Risk factors on water transport - Slatvinska, Valeriia M.; Слатвінська, Валерія Микoлaївна; Vasylenko, Mykola D.; Василенко, Микола Дмитрович (My University, 2021)
The subject of the study is transportation by waterways, in particular, the activity of sea and river transport in conditions of occurrence of unfavorable conditions, the interaction of the ship’s crew and the behavior of ship personnel when making decisions on water transport, manifestations of risky events and negative consequences on waterways, decision-making by the boat master in stressful, force majeure, regular and emergency situations.
Slatvinskaia V. M. Risk factors on water transport / V. M. Slatvinska, M. D. Vasilenko //«Priority areas for development of scientific research: domestic and foreign experience», 3-d edition, Izdevniecība “Baltija Publishing”, 2021. - С. 66-88. DOI: https://doi.org/10.30525/978-9934-26-049-0-34